Damiaan zijn wonder gaat verder - Van Puymbroeck, Rik; Merckx, Eddy; Verbruggen, Herman; Brahim; Vermassen, Jef; Jansen, Charlotte; Platteau, Jean; Dirven, Tim; Hendryckx, Michiel; De Veuster, Jozef sanctus, C.SS.CC. 1840-1889; Damiaanactie (Averbode Altiora, 2009)
Met bijdragen van Jef Vermassen, Eddy Merckx, Herman Verbruggen en Brahim.